Cellular mechanisms of metabolic syndrome-related atrial decompensation in a rat model of HFpEF. (February 2018) - Hohendanner, Felix; Bode, David; Primessnig, Uwe; Guthof, Tim; Doerr, Rafael; Jeuthe, Sarah; Reimers, Sophie; Zhang, Kun; Bach, Doris; Wakula, Paulina; Pieske, Burkert M.; Heinzel, Frank R.
Abstract: Heart failure (HF) with preserved ejection fraction (HFpEF) is present in about 50% of HF patients. Atrial remodeling is common in HFpEF and associated with increased mortality. We postulate that atrial remodeling is associated with atrial dysfunction in vivo related to alterations in cardiomyocyte Calcium (Ca) signaling and remodeling. We examined atrial function in vivo and Ca transients (CaT) (Fluo4-AM, field stim) in atrial cardiomyocytes of ZSF-1 rats without (Ln; lean hypertensive) and with metabolic syndrome (Ob; obese, hypertensive, diabetic) and HFpEF. Results: At 21 weeks Ln showed an increased left ventricular (LV) mass and left ventricular end-diastolic pressure (LVEDP), but unchanged left atrial (LA) size and preserved atrial ejection fraction vs. wild-type (WT). CaT amplitude in atrial cardiomyocytes was increased in Ln (2.9 ± 0.2 vs. 2.3 ± 0.2 F/F0 in WT; n = 22 cells/group; p < 0.05). Studying subcellular Ca release in more detail, we found that local central cytosolic CaT amplitude was increased, while subsarcolemmal CaT amplitudes remained unchanged. Moreover, Sarcoplasmic reticulum (SR) Ca content (caffeine) was preserved while Ca spark frequency and tetracaine-dependent SR Ca leak were significantly increased in Ln. Ob mice developed a HFpEF phenotype in vivo, LA area was significantly increased and atrial in vivo function was impaired, despite increased atrial CaT amplitudes in vitro (2.8 ± 0.2; p < 0.05 vs. WT). Ob cells showed alterations of the tubular network possibly contributing to the observed phenotype. CaT kinetics as well as SR Ca in Ob were not significantly different from WT, but SR Ca leak remained increased. Angiotensin II (Ang II) reduced in vitro cytosolic CaT amplitudes and let to active nuclear Ca release in Ob but not in Ln or WT. Summary: In hypertensive ZSF-1 rats, a possibly compensatory increase of cytosolic CaT amplitude and increased SR Ca leak precede atrial remodeling and HFpEF. Atrial remodeling in ZSF-1 HFpEF is associated with an altered tubular network in-vitro and atrial contractile dysfunction in vivo, indicating insufficient compensation. Atrial cardiomyocyte dysfunction in vitro is induced by the addition of angiotensin II. Highlights: Atrial remodeling is a hallmark feature of hypertension and HFpEF. Atrial function is preserved in hypertension related to enhanced Ca release. In metabolic HFpEF, atrial function is impaired. Atrial Ca homeostasis is altered in hypertension and HFpEF. Altered Ca homeostasis is related to changes of SR Ca release and the tubular network.